Primary Cutaneous Cryptococcosis Caused by Cryptococcus gatti in an Elderly Patient - Belda, Walter; Casolato, Ana T. S.; Luppi, Juliana B.; Passero, Luiz Felipe D. [UNESP]; Criado, Paulo R. (MDPI, 2022)
According to the spread of Cryptococcus sp., fungal infections can be classified as primary or secondary. In primary cutaneous cryptococcosis, the fungi are restricted to the skin of the patients, without systemic involvement. The incidence of primary cutaneous cryptococcosis is high in patients with immunosuppression, and this type of infection is rarely observed in patients who are immunocompetent. In the present case report, a patient who is immunocompetent and has systemic comorbidity reported that, after skin trauma, ulcerovegetative lesions appeared in the right upper arm; the etiologic agent was identified as Cryptococcus gatti, serotype B. The cutaneous lesions healed completely after 5 months of fluconazole treatment.
Keywords: cryptococcosis; cutaneous involvement; immunocompetent patient